Uji Virulensi Patogen Fusarium solani f.sp. cepae Pada Tanaman Bawang Merah (Allium ascalonicum L.) - Irna Il Sanuriza; Eti Kusumawati; Irfan Jayadi; Dwi Kartika Risfianty; Khaerul Ihwan; Baiq Naili Dewi Atika; Pahmi Husain (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2023)
Pathogens are one of the obstacles in shallot cultivation. One of them is Fusarium sp. which resulted in damage reaching more than 50-75%. The aim of this study was to determine the virulence level of the fungus Fusrium.solani.f.sp.cepae that causes fusrium wilt in shallot plants. The method used is an experimental method with a completely randomized design (CRD) with two treatments: method of application and time of observation/measurement. The average incubation period of fusarium wilt disease on shallots without F.solani.f.sp.cepae treatment had no symptoms of attack, while those that were treated showed symptoms in a short time. The results showed that the pathogen F.solani.f.sp.cepae was able to attack plants with an average attack intensity of 4.22, meaning high attack intensity. Macroscopically identification of fungi that had grown on potato dextrose agar (PDA) medium was observed, observations starting from the shape of the mushroom colonies and the color of the underside of the mushroom colonies, while microscopically found insulating hyphae, forming branching and found macroconidia and microconidia spores.